KUFRI LOHIT: A NEW RED SKIN POTATO VARIETY - Luthra, Satish Kumar (Potato Journal, 2023)
ABSTRACT: Kufri Lohit is a red skin, medium maturing, main season, high yielding table potato variety recommended forcultivation in North-Indian plains (Eastern & Central plains). It can also successfully be grown in northern plains to meetthe seed potato demands of regions that prefer red skin tubers. It is a clonal selection of a cross between Kufri Kanchanand Kufri Khyati. Its plants are medium tall and vigorous having field resistance to late blight. It produces attractive redcoloured, ovoid tubers with shallow eyes, cream flesh, and mealy texture. This variety possesses approximately 18% tuberdry matter content and has very good keeping quality. It is responsive to crop nutrition and yields 36–38 t/ha total tuberyield under optimum crop management.